EKSPLORASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM ANTOLOGI CERPEN PILIHAN KOMPAS ID EDISI OKTOBER 2025 - Rosdayana; Suhardi; Leoni, Tessa Dwi; Malik, Abdul; Lolita, Asri; Mustado, Maulida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education plays a strategic role in developing students who possess moral integrity, social responsibility, and ethical awareness. Literary works, particularly short stories, serve not only as artistic expressions but also as educational media that convey character values through narratives, characters, conflicts, and moral messages. This study aimed to analyze the character education values represented in the Kompas.id Selected Short Story Anthology, October 2025 Edition. The research employed a descriptive qualitative approach. The research object was the anthology, while the data consisted of words, phrases, sentences, dialogues, narratives, and characters' actions indicating character education values. Data were collected through documentation using reading and note-taking techniques and analyzed through data identification, classification, interpretation, and description based on the eighteen character education values formulated by the Indonesian Ministry of National Education (Kemendiknas, 2010). The findings revealed ten character education values represented in the anthology, namely religiousness, honesty, hard work, independence, curiosity, friendliness/communicativeness, reading interest, environmental awareness, social awareness, and responsibility. These values were reflected through the characterization, plot, dialogue, conflict, and moral messages embedded in the stories. The findings indicate that the anthology possesses not only aesthetic value but also educational value, making it a relevant literary resource for strengthening character education and supporting Indonesian language learning.